Pengaruh Ice breaking terhadap Minat Belajar Siswa Kelas V SD Negeri 10 Manurunge Kecamatan Tanete Riattang Kabupaten Bone - rosmalah rosmalah; hasdiana hasdiana; satriani satriani (Universitas Negeri Makassar, 2019)
The problem in this study is the low interest in learning of fifth grade students at SDN 10 Manurunge, Tanete Riattang, Bone District. The formulation of the problem in this study is how the description of Student Interest in Class V of the 10th Elementary School Manurunge Tanete Riattang, Bone District and whether there is a significant influence on the application of Ice breaking on student learning interest. The purpose of this study was to describe the interest in learning for fifth grade students at SDN 10 Manurunge Tanete Riattang sub-district, Bone Regency, then to find out the picture of students' learning interest after applying ice breaking to fifth grade students at Manurunge 10 Public Elementary School, and to determine the effect of ice breaking towards student learning interest. The research approach is a quantitative approach. This type of research is quasi-experimental research in the form of a non-equivalent control group design. There are two research variables namely the independent variable (ice breaking) and the dependent variable (learning interest). The total population is 96 students. The research sample was selected using a purposive sampling technique. Data collection techniques in this study used a questionnaire and documentation. Data was collected by giving Pre-test and Post-test and analyzed using descriptive statistics and inferential statistics. Based on the analysis results obtained sig. (2 tailed) 0,000 <0.05 which means that there are significant differences in the average student interest in learning, so it can be concluded that ice breaking has a significant effect on student interest in learning.